Preemptive Analgesic with Paracetamol and Tramadol Analgesics in Pediatric Circumcision - Ardi Pramono; Gibran Raka Pramodya; Cornel Anggara; Amaro Yudho Wibowo (JKKI (Jurnal Kedokteran dan Kesehatan Indonesia), 2018)
Background: Circumcision is the most widely minor surgery in the world, whether done by doctors, paramedics, or by traditional. Circumcision that removes part or all of the penis prepuce with the aim of removing smegma (dirt). Society circumcised their children at the age of 5-12 years. Analgesics may be given to patients, for instance, paracetamol, nonsteroidal anti-inflammatory drug (NSAIDs) such as aspirin and opioid groups such as tramadol. Objective: The aim of this study was to compare the effectiveness of paracetamol analgesics and tramadol in circumcised patients given prior to the act of circumcision. Methods:This study was a quasi-experimental study to determine different analgesic effects of paracetamol and tramadol administration, prior to circumcision. The subjects of this study are children aged 5-12 years as many as 36 children, which is divided into 2 groups of paracetamol and tramadol group. One hour before circumcision, subjects were given group-appropriate analgesics, then the Visual Analog Scale (VAS) was measured 1 hour after circumcision. The data obtained were made intopercentage on the scale of VAS <5 and> 5. Results:Â In the paracetamol group, there were 5 children (27.8%) with VAS 1-3 (mild pain), 13 children (72.2%) with moderate pain (VAS value 4-7). In the tramadol group, there were 15 children (83.3%) with mild pain (VAS score 1-3), and the remaining 3 children (16.7%) had moderate pain. No side effects of both analgesic drugs were found. Conclusion: Patients with mild pain complaints were more likely found in the tramadol group than in paracetamol group. Tramadol gave stronger preemptive analgesic results in circumcision compared to paracetamol.